OFR-139-81 Development Of Improved Detection Instruments For Toxic Gas Contaminants In Mining Atmospheres - J. A. Kosek (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Work has been carried out under Bureau of Mines Contract No. HO395132 to develop and fabricate gas sensors for mining applications. Promising new instruments have been designed, developed, tested and supplied to meet BuMines requirements. These instruments include prototype 1) remote-sensing, diffusion-type CO monitors for mine operation which can be operated in conjunction with a surface computer, 2) control modules for alternate in-mine readout of the remote diffusion type CO monitors, 3) personal CO diffusion-type dosimeters and 4) personal NO diffusion-type dosimeters. In addition, retrofit modifications were made to update and optimize operation of CO and NO2 direct-reading type detectors provided under a previous contract. Studies were conducted to evaluate and demonstrate the availability of stable, portable N02 calibration sources for NO2 instrumentation. The use of selected, commercially available cylinder sources for NO2 instrument calibration were recommended. Additional studies were also conducted to investigate the feasibility of instrumentation for rapidly monitoring CO, NO and NO2 in diesel exhaust.